2017
DOI: 10.4103/2045-9912.202912
|View full text |Cite
|
Sign up to set email alerts
|

Co-administration of tissue plasminogen activator and hyperbaric oxygen in ischemic stroke: a continued promise for neuroprotection

Abstract: Intravenous recombinant tissue-type plasminogen activator (r-tPA, alteplase) remains the recommended therapy for acute ischemic stroke. However, several factors are limiting its practical use. It makes it urgent for us to search more efficient strategies that can save the ischemic neurons, and safely extend the time window, while in the mean time reducing the detrimental effects for stroke thrombolysis. Hyperbaric oxygen therapy (HBOT) is considered to be potentially neuroprotective. Co-administration of r-tPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
0
6
0
1
Order By: Relevance
“…Therefore, sufficient oxygen in the air is very important for the normal growth and development of animals. Experimental studies found that O 2 supplementation has some beneficial effects including neuroprotective 35 , ischemic tissue 36 , angiogenesis and wound healing 12 , 13 . However, whether O 2 supplementation has a promoting effect on the growth of TBCs or ameliorating effect on hypoxia-suppressed weight gain is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, sufficient oxygen in the air is very important for the normal growth and development of animals. Experimental studies found that O 2 supplementation has some beneficial effects including neuroprotective 35 , ischemic tissue 36 , angiogenesis and wound healing 12 , 13 . However, whether O 2 supplementation has a promoting effect on the growth of TBCs or ameliorating effect on hypoxia-suppressed weight gain is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Although hyperbaric oxygenation (HBO) therapy is not recommended by American Heart Association and Stroke Association guidelines (Jauch et al, 2013; Misir et al, 2017), HBO therapy is a widely used non-pharmacologic and non-invasive clinical treatment of ischemic stroke (Hu et al, 2014; Yang and Mu, 2017). It enhances oxygen supply, stabilizes the BBB, and decreases infarct size and cerebral edema in global or focal ischemia stroke (Neumann-Haefelin et al, 2000; Veltkamp et al, 2005).…”
Section: Recently Identified Therapeutic Aims and Therapiesmentioning
confidence: 99%
“…Lack of blood supply deprives the brain cells of necessary glucose and oxygen, and disturbs cellular homeostasis, culminating in neuronal death. Currently, tissue plasminogen activator (tPA) is the only effective pharmacological therapy approved by the Food and Drug Administration for acute ischemic stroke since 1996, but its use remains limited due to the narrow therapeutic window [ 3 - 6 ]. It is imperative to develop novel therapeutic strategies of stroke [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%